2019
DOI: 10.1002/ijc.32350
|View full text |Cite
|
Sign up to set email alerts
|

Prediagnostic blood levels of organochlorines and risk of non‐Hodgkin lymphoma in three prospective cohorts in China and Singapore

Abstract: Specific organochlorines (OCs) have been associated with non‐Hodgkin lymphoma (NHL) with varying degrees of evidence. These associations have not been evaluated in Asia, where the high exposure and historical environmental contamination of certain OC pesticides (e.g., dichlorodiphenyltrichloroethane [DDT], hexachlorocyclohexane [HCH]) are different from Western populations. We evaluated NHL risk and prediagnostic blood levels of OC pesticides/metabolites and polychlorinated biphenyl congeners in a case–control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A study of prediagnostic serum concentrations of organochlorines, including β‐ and γ‐HCCH, in a cohort from Maryland found no association with NHL risk, however, this analysis was based on a small number of cases 48 . More recently, a pooled analysis of East Asian cohorts with substantially higher blood concentrations of organochlorines than in Western populations, reported a significant association between β‐HCCH levels and NHL risk, but not p,p′‐DDE levels 49 …”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A study of prediagnostic serum concentrations of organochlorines, including β‐ and γ‐HCCH, in a cohort from Maryland found no association with NHL risk, however, this analysis was based on a small number of cases 48 . More recently, a pooled analysis of East Asian cohorts with substantially higher blood concentrations of organochlorines than in Western populations, reported a significant association between β‐HCCH levels and NHL risk, but not p,p′‐DDE levels 49 …”
Section: Discussionmentioning
confidence: 92%
“…48 More recently, a pooled analysis of East Asian cohorts with substantially higher blood concentrations of organochlorines than in Western populations, reported a significant association between β-HCCH levels and NHL risk, but not p,p 0 -DDE levels. 49 In contrast to studies of well-characterized organochlorine compounds, fewer studies have examined pyrethrins and other inorganic agents. We observed a fivefold increase in FL risk associated with 10 or more years of pyrethrum use, as well as significant associations with ever use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of target analyses was performed using a chromatography isotope dilution high resolution mass spectrometer (GC-IDHRMS). Case-control pairs were analyzed sequentially in the sequential batch and laboratory workers were blinded according to the control status of the samples [25].…”
Section: Measurement Tools Usedmentioning
confidence: 99%
“…Cancer records [19], SEER coding scheme for the classification of NHL and its subtypes [19], WHO Lymphoma Classification [23], International Classification of Oncology [24], InterLymph Consortium Classification [6], socio-demographic information questionnaire form [19,23,24], questionnaire form examining the use of pesticides [6,19,24], CAREX database [23] were used. Gas chromatograph and chemistry analyzer were used to perform laboratory analyses in two studies [25,26]. It was found that the use of herbicides had a small but significant effect on the risk of some NHL subtypes, however, it did not affect the risk of NHL in general.…”
Section: Measurement Tools Usedmentioning
confidence: 99%